Challenges and Barriers in Implementing Community Health Education Faced by BSN Students at the College of Nursing, Sir C.J Institute of Psychiatry, Hyderabad - Junejo, Zafarullah; Talpur, Mushtaque Ali; Chandio, Irfan Ali; Soomro, Farzana; Rai, Yaswant; Korai, Smina Parveen; Khowaja, Zohra (Biological and Clinical Sciences Research Journal, 2025)
Health education empowers individuals to enhance their health knowledge and make health-related decisions. Objective: This research aimed to assess the challenges and barriers BSN students face in implementing community health education. Methods: The descriptive non-experimental design was the research methodology employed in this study from September 17 to December 23, 2024. The study was conducted with 106 BSN students from the College of Nursing at Sir C.J. Institute of Psychiatry, Hyderabad. A structured questionnaire was utilised to identify the challenges and barriers to health education. In IBM SPSS version 23, descriptive statistics were used to analyse the data as frequencies and percentages. Results: Major challenges included managing diverse client groups, preparing appropriate audiovisual aids, addressing clients’ time limitations, finding suitable session venues, and balancing additional clinical assignments. Significant barriers were identified, such as difficulties translating medical terminology into the local language, noise, environmental distractions, challenges in controlling external factors, and insufficient time to evaluate the client’s knowledge effectively. Conclusion: The study concluded that BSN students encounter various challenges and barriers in delivering health education, relating to students, teaching materials, audiovisual aids, clients, environmental factors, and evaluation processes. Identifying these challenges is essential for developing strategies to overcome them, ultimately facilitating more effective health education in community settings.